MAYA ANGELOU'S HABITUS IN AFRO-AMERICAN SOCIETY ON THE NOVEL 'I KNOW WHY THE CAGED BIRD SINGS' (Universitas Negeri Semarang, 2022)
I Know Why the Caged Bird Sings is an autobiography novel about life of Maya Angelou, a well-known African American writer, poet, to the activist of civil rights who has experienced various problems such as bullying and sexual harassment. This work created by Maya herself that talks about her struggle, thoughts and habits brought her to the successful in American Society. This study is type of descriptive qualitative with aims to analyze and identify Maya’s Habitus using the perspective of Pierre Bourdieu. The findings and discussion showed that there were several habitus that Maya did to make her become one of the great writers of the United States. The habitus is meticulous, diligent, courageous, intelligent, and love reading and writing. Those Habitus motivated by several things including racist treatment that encourages Maya become a brave figure against it. Habitus diligently worked due to the Maya’s condition who came from family with low economic capital and her parent who get divorced. Habitus like reading and writing caused by psychological trauma faced after Maya getting sexually abused and experiencing rape. All the bad things that Maya faced then turned out to be good things after she successfully used her thoughts, tastes and habitus.